#MeToo, sexual harassment: an article, a forum, and a dream for the future. Issue 2 (4th March 2019) - Clair, Robin Patric; Brown, Nadia E.; Dougherty, Debbie S.; Delemeester, Hannah K.; Geist-Martin, Patricia; Gorden, William I.; Sorg, Tyler; Turner, Paaige K.
ABSTRACT: #MeToo has breathed new life into the women's movement and especially into understanding and rectifying sexual harassment, abuse and assault. It has galvanized activists around the globe. And it has placed thousands of stories of the harassed in full view of the public. Sexual harassment, abuse and assault may occur within the organizational context or beyond; but sexual harassment, in particular has been legally labeled an organizational phenomenon. With this in mind, Robin Clair frames the early part of this article around the most recent organizational communication theories (see the appendix for an overview of these theories). Following the essay is a forum, in which invited scholars address questions related to the #MeToo movement.